Investigating falsified vehicle documentation (Academic Journal of Internal Affairs, 2018)
The author provides a description of a trasological search-based case study of the forensic examination of a vehicle document and dynamic toolmarks in particular.
Keywords: case study; vehicle documentation; adulteration